مائٹو کونڈریا ٹرانسپلانٹ کے اخلاقی اقدارپر اثرات کا جائزہ (Al-Aasar, 2025)
Mitochondrial transplant is the latest advancement in In Vitro Fertilization (IVF). It primarily aims to protect newborns from incurable mitochondrial diseases, which are inherited from the mother. If a mother suffers from mitochondrial disorders, the risk of passing these genetic defects to her child is high. To prevent this, genetic modifications are made in the mother’s egg by removing its nucleus and transferring it into the cytoplasm of a healthy donor egg. The resulting child is often referred to as a "three-parent baby."There are two primary techniques for mitochondrial transplant:• Spindle Nuclear Transfer: In this method, the nucleus from the mother’s egg is transferred into a healthy donor egg, from which the nucleus has already been removed.• Pronuclear Transfer: This technique involves transferring the nucleus of a fertilized egg (from both parents) into a fertilized donor egg, after removing its original nucleus.Western countries have already legalized mitochondrial transplants, and research is also progressing in India. However, the Muslim world has raised significant ethical and religious concerns regarding this procedure. The primary objection is that donating one woman’s egg to another interferes with divine creation, causes lineage confusion, and disrupts the family system. It also raises ethical and legal dilemmas regarding parentage and inheritance.Although some contemporary scholars argue for its permissibility under the principle of Maqāṣid al-Sharī‘ah (preservation of essential objectives of Islamic law), leading Islamic jurists have rejected this argument, asserting that it compromises the child's rights. Various Islamic legal bodies, such as the International Islamic Fiqh Academy (1990) and Islamic Research Academy (1997), have declared mitochondrial transplants impermissible. Hence, there is a consensus among contemporary Islamic scholars that donating any organ carrying genetic or hereditary traits is prohibited.